The Economic Impact of Heritable Physical Traits: Hot Parents, Rich Kid? - Daniel S. Hamermesh; Anwen Zhang (Institute of Labor Economics (IZA), 2024)
Since the mapping of the human genome in 2004, biologists have demonstrated genetic links to the expression of several income-enhancing physical traits. To illustrate how heredity produces intergenerational economic effects, this study uses one trait, beauty, to infer the extent to which parents' physical characteristics transmit inequality across generations. Analyses of a large-scale longitudinal dataset in the U.S., and a much smaller dataset of Chinese parents and children, show that a one standard-deviation increase in parents' looks is associated with a 0.4 standard-deviation increase in their child's looks. A large data set of U.S. siblings shows a correlation of their beauty consistent with the same expression of their genetic similarity, as does a small sample of billionaire siblings. Coupling these estimates with parameter estimates from the literatures describing the impact of beauty on earnings and the intergenerational elasticity of income suggests that one standard-deviation difference in parents' looks generates a 0.06 standard-deviation difference in their adult child's earnings, which amounts to additional annual earnings in the U.S. of about 2300.
Keywords: D64; D31; J71; 330; intergenerational transmission; inequality; beauty